Hungarian Monitoring, 13 December 1989 . [Magyar rádiófigyelő], 1989. december 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Czechoslovak parliament in session - Extraordinary Party congress in Bulgaria - USSR: Ryzhkov's economic program; Gorbachev's position - Rakowski must answer to the courts - Ceauşescu and his opponents Domestic Affairs: - Miklós Németh-Margaret Thatcher meeting - Horn in Brussels - Hungarian-Vatican diplomatic relations - Gabčíkovo-Nagymaros dam affair - The László Tőkés case - Parliamentary committee meetings - György Krassó occupies HQ building - Interview on the question of apportioning responsibility Economy: - TOT meeting - Veszprém County State Construction Company to be wound up Külpolitika: - Csehszlovák parlament ülése - Rendkívüli pártkongresszus Bulgáriában - SZU: Rizskov gazdasági programja; Gorbacsov pozíciója - Rakowskinak a bíróság előtt kell felelnie - Ceauşescu és ellenzéke Belpolitika: - Németh Miklós-Margaret Thatcher találkozó - Horn Brüsszelben - Magyar-vatikáni diplomáciai kapcsolatok - Bős-Nagymarosi vízlépcső ügy - Tőkés László ügy - Országgyűlési bizottsági ülések - Krassó György székházfoglalója - Interjúk a felelősségre vonás kérdéséről Gazdaság: - TOT ülés - A VÁÉV felszámolása